Математична модель удосконаленого регулятора витрати рідини - Андренко, Павло Миколайович; Гречка, Ірина Павлівна; Клітной, Віктор Володимирович; Хованський, Сергій Олександрович (Таврійський державний агротехнологічний університет ім. Д. Моторного, 2020)
Показана конструктивна схема удосконаленого регулятора витрати рідини, особливістю якого є те, що у його нижній частині, перед нижньою глухою торцевою камерою клапана тиску, виконана додаткова проточна циліндрична камера. У цій камері на циліндричному золотнику клапана тиску, перпендикулярно до нього, встановлено реактивну турбіну типу «сегнерівське колесо». З боку гострої дроселюючої кромки золотника клапана тиску у проточній камері регулятора виконано розточку еліпсоподібної форми. Уперше отримана повна математична модель розробленого регулятора, яка крім його конструктивних параметрів ураховує його конструктивні параметри, параметри робочої рідини, характер зміни навантаження у гідроагрегаті. Розроблена математична модель робочого процесу регулятора витрат дозволяє визначити його статичні і динамічні характеристики та проаналізувати вплив на них конструктивних параметрів регулятора і робочих параметрів гідроагрегату.

A structural diagram of an improved fluid flow regulator is shown, which, due to the increased sensitivity of the regulator pressure valve spool to changes in pressure drop in its deaf chambers, is able to accurately maintain a constant flow rate at its output under a changing load on the hydraulic unit's actuator. A feature of the developed regulator is that in its lower part, in front of the lower deaf end chamber of the pressure valve, an additional flow-through cylindrical chamber is made parallel to it, the input of which is the input of the fluid flow regulator, and the output is connected by a channel made in the flow regulator to the valve input pressure. In this flow chamber of a valve mounted by a jet turbine of the Segner wheel type. On the side of the sharp throttling edge of the pressure valve spool, in the flow chamber of the fluid flow regulator, an ellipsoid-shaped sprout is made, the axis of which forms an acute angle equal to α with the axis of the pressure valve spool, the value of which is in the range 59–68°. For the first time, a complete mathematical model of the developed improved fluid flow controller was obtained, which, in addition to the design parameters of the flow controller, takes into account its design parameters, working fluid parameters, and the nature of the change in the flow rate of the load in the hydraulic unit. The developed mathematical model of the workflow of the flow controller allows you to determine its static and dynamic characteristics and analyze the effect on them of the design parameters of the flow controller and operating parameters of the hydraulic unit. The use of the developed fluid flow regulator in a hydraulic unit allows to increase its technical level.
Mathematical model of the improved liquid flow regulator
Keywords: регулятор витрати; математична модель; характеристики; клапан тиску; регульований дросель; сегнерівське колесо; робоча рідина; сила тертя; гідродинамічна сила; flow regulator; mathematical model; characteristics; pressure valve; adjustable throttle; segner wheel; working fluid; friction force; hydrodynamic force